Purinergic signaling via P2X receptors and mechanisms of unregulated ATP release in the outer retina and age-related macular degeneration - Molcak, Haydn; Jiang, Kailun; Campbell, Christopher J.; Matsubara, Joanne A. (Frontiers in Neuroscience, 2023)
Age-related macular degeneration (AMD) is a chronic and progressive inflammatory disease of the retina characterized by photoceptor loss and significant central visual impairment due to either choroidal neovascularization or geographic atrophy. The pathophysiology of AMD is complex and multifactorial, driven by a combination of modifiable and non-modifiable risk factors, molecular mechanisms, and cellular processes that contribute to overall disease onset, severity, and progression. Unfortunately, due to the structural, cellular, and pathophysiologic complexity, therapeutic discovery is challenging. While purinergic signaling has been investigated for its role in the development and treatment of ocular pathologies including AMD, the potential crosstalk between known contributors to AMD, such as the complement cascade and inflammasome activation, and other biological systems, such as purinergic signaling, have not been fully characterized. In this review, we explore the interactions between purinergic signaling, ATP release, and known contributors to AMD pathogenesis including complement dysregulation and inflammasome activation. We begin by identifying what is known about purinergic receptors in cell populations of the outer retina and potential sources of extracellular ATP required to trigger purinergic receptor activation. Next, we examine evidence in the literature that the purinergic system accelerates AMD pathogenesis leading to apoptotic and pyroptotic cell death in retinal cells. To fully understand the potential role that purinergic signaling plays in AMD, more research is needed surrounding the expression, distribution, functions, and interactions of purinergic receptors within cells of the outer retina as well as potential crosstalk with other systems. By determining how these processes are affected in the context of purinergic signaling, it will improve our understanding of the mechanisms that drive AMD pathogenesis which is critical in developing treatment strategies that prevent or slow progression of the disease.